Modelling the effective atomic number and the packing factor of polyatomic compounds: Applications to refractive index and dosimetry. (September 2016) - Lima, H.; Couto dos Santos, M.A.
Abstract: In this work, based on fundamental physics and chemistry (charge distribution, electronegativity, induced dipole moment), we are introducing an analytical expression for Z eff and a general way of calculating the crystal packing factor, p, of any ionic material. By using the average separation between the atomic and crystal(ionic) radii of the interacting ions, we are postulating an effective distance ( R ij ) between the positive and the negative centre of charge. When compared to the available experimental data, predictions within 20% have been obtained to Z eff of materials applied to dosimetry. In photonics, the increasing behaviour of the refractive index with Z eff is confirmed. By combining crystal field and effective charge models, we have predicted Z eff of the Eu2 O3 within the range of available experimental data. Abstract : Highlights: An analytical expression to predict the effective atomic number of any ionic compound is being announced. An effective distance between the positive and negative centre of charge is being postulate.